Estrategias didácticas y su incidencia en la lectura comprensiva en los estudiantes de Básica Media del Centro Educativo “Calicuchima” del cantón Quinsaloma provincia los Ríos - Macías Macías, Nixi Violeta (2017)
The research work carried out and called comprehensive reading as a didactic strategy and its impact on meaningful learning in the middle school students of the "Calicuchima" educational center, in the canton of Quinsaloma, proposes to apply appropriate active methods and techniques in accordance with the need to have with a teaching methodology so that the teacher chooses strategies that he considers the most appropriate, that the type of content to be taught prevails in the area, so that the methodological strategy allows not only the teacher to arrive in a clear way but also helps the student to build their own learning constructively. Comprehensive reading is indispensable for the student. This is something that he himself is discovering as he progresses in his studies. At the primary level and, to a lesser extent, at the intermediate level, it sometimes reaches a minimum level of understanding and a good memory, but as one goes to the study of more complex topics, a good memory is not enough. When thinking, concepts, data and information are related, establishing causal relations or comparisons among them, classifying them, bringing them together under a general explanation that encompasses and surpasses them. One of the big resumes that education has to assume is to promote strategies that allow students to develop their reading and potential in a more meaningful and constructive way. Taking into account that not only the student is responsible for learning, but also the educator since he is responsible for the educational process and the time devoted to it, together with the context where it is generated, develops the school interaction